AWARENESS, ACCESSIBILITY, AND ACADEMIC UTILITY OF E-SHODHSINDHU RESOURCES AMONG ACADEMICS IN TECHNICAL INSTITUTIONS OF KARNATAKA. - Mr. Jagadeesha S; Kaur, Purushothama Gowda M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid proliferation of information and communication technology (ICT) has significantly influenced academic research, enabling access to extensive digital repositories like the e-ShodhSindhu consortium in India. This study assesses the awareness, accessibility, and academic utility of e-ShodhSindhu resources among academic stakeholders in selected technical institutions in Karnataka, namely NITK Surathkal, IIT Dharwad, and IISc Bangalore. A quantitative approach was employed, using Krejcie and Morgan’s (1970) formula to determine a sample size of 1184 respondents, comprising students, faculty members, and research scholars. Data were collected through a structured questionnaire addressing demographic information, awareness, usage patterns, academic impact, challenges, training needs, and satisfaction levels. Analysis revealed that while awareness of e-ShodhSindhu resources is high (96.54%), usage patterns indicate sporadic engagement, with most respondents accessing resources occasionally. E-journals and databases emerged as the most utilized resources, whereas reference works and digital archives exhibited lower engagement. The findings underscore the need for targeted training programs and enhanced infrastructure to optimize resource utilization, thereby aligning academic resource access with research productivity goals.